491 Production factors affecting the contribution of collagen to meat toughness. (7th December 2018) - Bruce, H; Roy, B
Abstract: The progression of mature collagen crosslink formation in bovine intramuscular connective tissue (IMCT) is affected by growth promotants use and cattle age. One-way analysis of variance of data from gluteus medius (GM) and semitendinosus (ST) muscles from 14 calf-fed (about 14 months) and 14 yearling-fed (about 20 months) steers, and 12 mature cows (> 3 years) of Charolais Red-Angus or Hereford-Aberdeen Angus genetics indicated collagen heat solubility was significantly (P < 0.05) reduced in both muscles from mature cows compared to calf- and yearling-fed steers, and that total collagen increased with cattle age in the GM only. Pyridinoline (Pyr) concentrations and densities increased in the IMCT of GM of steers to the same levels of those of cow IMCT by the yearling-fed stage while Ehrlich Chromogen (EC) concentration was lowest in cows regardless of muscle. Mean thermal denaturation temperatures (Tmax, °C) for IMCT were similar for calf- and yearling-fed steers regardless of muscle, but were significantly increased for both muscles from cows. Pearson correlations showed that GM WBSF was unrelated to collagen characteristics, but ST WBSF was negatively correlated to EC concentration (mol EC/g raw meat)(r = -0.41, P 0.01) and density (mol EC/mol collagen)(r = -0.32, P 0.05), and collagen solubility (%, r = -0.48, P 0.01), and positively correlated to IMCT Tmax (r = 0.63, P 0.0001) and enthalpy (kJ/mol)(r = 0.58, P 0.0001). Tmax was positively correlated to Pyr density (mol Pyr/mol collagen, r = 0.50 and 0.53, P 0.001, GM and ST, respectively) and negatively correlated to EC density (mol EC/mol collagen, r = -0.52 and -0.70, P 0.0001, GM and ST respectively). These results suggested that Pyr contributes to WBSF of high IMCT locomotory muscles such as the ST more than to that of postural muscles such as the GM.